LITERATUR REVIEW: BEBERAPA FORMULASI DARI ASAP CAIR - Zebua, Nilsya Febrika; Nadia, Syarifah; Elviana, Elviana (Universitas Imelda Medan, 2024)
Liquid smoke is the result of condensation or direct combustion produced from materials containing lignin, cellulose, hemicellulose and other carbon compounds. Based on the literature read, it turns out that there are many contents of liquid smoke, one of which is as a preservative. The method used in this research is the literature review method where this method can help in terms of inputting data in detail and clearly. The results of this study state that liquid smoke can be used in preservative, antibacterial and deodorizing latex preparations. The purpose of this research is to find out how many uses for liquid smoke so that it can be used in everyday life. The conclusion in this study is that liquid smoke is most widely used in preservatives which distinguishes the method used in the form of a literature review.